APLIKASI TEORI STRUKTURALISME GENETIK, FEMINISME, SASTRA & POLITIK, TEORI HEGEMONI, RESEPSI SASTRA DALAM PENELITIAN MAHASISWA - Mateus Rudi Supsiadji (Universitas 17 Agustus 1945 Surabaya, 2011)
Abstract. This article discusses the weaknesses of studentâ€™s comprehension on theories that they were applying on their research. The result of the analysis were: 1) in applying genetic structuralism the students did not relate the structure of a literary work with the structure of the society on the issue; 2) they did not state clearly their stand points in applying feminist criticism; 3) in applying the political-ideology criticism, the students explained nothing on the authorâ€™s strategies to bring out his or her political-ideology; 4) in their applying theory of hegemony, the students were unclearly to choose the interested perspectives; 5) the students were not appropriately to choose the audience of which they addressed, and did not clearly state â€œthe horazone of the readerâ€™s expectationâ€, â€œopen spaceâ€, ; 6) the students did not clearly discussed the text norms, readerâ€™s knowledge and reading experiences, the tensions appearing between fiction and reality in a literary work in applying redearâ€™s reception. Each theory has its own principle characteristics in approaching a literary work.Â Key words: mastering theories, applying theories, sociological approach, feminism, readerâ€™s reception